2019
DOI: 10.3389/fphys.2019.00615
|View full text |Cite
|
Sign up to set email alerts
|

Triceps Surae Muscle-Tendon Unit Properties in Preadolescent Children: A Comparison of Artistic Gymnastic Athletes and Non-athletes

Abstract: Knowledge regarding the effects of athletic training on the properties of muscle and tendon in preadolescent children is scarce. The current study compared Achilles tendon stiffness, plantar flexor muscle strength and vertical jumping performance of preadolescent athletes and non-athletes to provide insight into the potential effects of systematic athletic training. Twenty-one preadolescent artistic gymnastic athletes (9.2 ± 1.6 years, 15 girls) and 11 similar-aged non-athlete controls (9.0 ± 1.7 years, 6 girl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 85 publications
2
19
1
2
Order By: Relevance
“…However, a significant relationship between muscle strength and tendon stiffness does not give evidence to a balanced adaptation within the MTU, because a high or low relationship does not provide any information concerning the margin of tolerated mechanical tendon loading during MVCs. There is experimental evidence of imbalances between muscle strength and tendon stiffness in competitive athletes from child- to adulthood due to different alterations of muscle and tendon properties, resulting in remarkably high or low tendon strain values ( Mersmann et al, 2016 ; Charcharis et al, 2019 ; Pentidis et al, 2019 ). Those imbalances indicate the relevance of an individualized training control and regulation.…”
Section: Framework Of the Individualized Muscle-tendon Assessment Andmentioning
confidence: 99%
“…However, a significant relationship between muscle strength and tendon stiffness does not give evidence to a balanced adaptation within the MTU, because a high or low relationship does not provide any information concerning the margin of tolerated mechanical tendon loading during MVCs. There is experimental evidence of imbalances between muscle strength and tendon stiffness in competitive athletes from child- to adulthood due to different alterations of muscle and tendon properties, resulting in remarkably high or low tendon strain values ( Mersmann et al, 2016 ; Charcharis et al, 2019 ; Pentidis et al, 2019 ). Those imbalances indicate the relevance of an individualized training control and regulation.…”
Section: Framework Of the Individualized Muscle-tendon Assessment Andmentioning
confidence: 99%
“…The pubertal status of the participants was assessed by their parents, by determining the Tanner stage according to drawings of the respective features Tanner 1969, 1970). At the time of data acquisition, the training intensity and volume of the athletes had been documented for the last 6 months and averaged to ∼ 5 h of specific muscle strength and jumping training and ∼ 12 h of main on-apparatus gymnastic training per week, including plyometric and landing exercises (for a detailed description of the training see Pentidis et al 2019).…”
Section: Participants and Experimental Designmentioning
confidence: 99%
“…Therefore, we can argue that additional investigations examining the effects of systematic resistance training on muscle hypertrophy in preadolescence are needed to better understand musculotendinous adaptive responses in this age. The athletic training in artistic gymnastics is characterised by a high volume of exercises requiring a high level of muscle strength exertion like jumping, landing, and movements on the apparatus in the age before puberty (Pentidis et al 2019), and is, therefore, appropriate for the investigation of possible training-induced hypertrophy in preadolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been attempted previously to investigate the growth changes in structural properties (length and cross-sectional area) of tendons (Kubo, Teshima, Hirose, & Tsunoda, 2014a, 2014bO'Brien, Reeves, Baltzopoulos, Jones, & Maganaris, 2010;Neugebauer & Hawkins, 2012;Mersmann et al, 2014Mersmann et al, , 2017Mogi et al, 2018;Waugh, Blazevich, Fath, & Korff, 2012. ), however, there is few information on the structural properties of the tendons at and/or around adolescent growth spurt (Charcharis, Mersmann, Bohm, & Arampatzis, 2019;Mogi et al, 2018;Mogi, 2019;Pentidis et al, 2019), and no studies have simultaneously examined the structural properties of both the Patellar and Achilles tendons at around adolescent growth spurt. have demonstrated that cross-sectional area of the Achilles tendon in distal region was greater than that of proximal region, and stated that region-specific hypertrophy in cross-sectional area of tendon occurs in response to the habitual loading.…”
Section: Introductionmentioning
confidence: 99%